2015
DOI: 10.1080/02763893.2015.989767
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of a “Sense of Community” in a Finnish Senior Co-Housing Community

Abstract: In the foreseeable future, alternative housing options will be needed to meet the needs of and answer to the wishes of older people. Cohousing schemes are developed to fulfill the need for a housing type that provides mutual support and social contacts while alleviating the isolation and loneliness often experienced in ordinary neighborhoods. This study on a senior co-housing community in Finland asked what a "sense of community" meant to the residents and how a sense of community becomes visible in daily life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
2
31
0
2
Order By: Relevance
“…I en studie av Jolanki och Vilkko (2015) framkom att invånarna i seniorboenden upplevde att den ömsesidiga hjälpen och stödet var en viktig del av samhörighetskänslan i och med att man kände sig behövd. Känsla av samhörighet har även samband med känsla av likvärdighet, med möjlighet att lära sig av varandra och ett stärkt socialt kapital ( Jolanki & Vilkko 2015). Det har visat sig att social gemenskap stärker både det fysiska och det psykiska välbefinnandet ( Jolanki m.fl.…”
Section: Inledningunclassified
See 1 more Smart Citation
“…I en studie av Jolanki och Vilkko (2015) framkom att invånarna i seniorboenden upplevde att den ömsesidiga hjälpen och stödet var en viktig del av samhörighetskänslan i och med att man kände sig behövd. Känsla av samhörighet har även samband med känsla av likvärdighet, med möjlighet att lära sig av varandra och ett stärkt socialt kapital ( Jolanki & Vilkko 2015). Det har visat sig att social gemenskap stärker både det fysiska och det psykiska välbefinnandet ( Jolanki m.fl.…”
Section: Inledningunclassified
“…Att samhörighet och socialt deltagande, eller till exempel gemensam sysselsättning, har ett samband med varandra, har konstaterats även i andra studier (Levasseur m.fl. 2017;Jolanki & Vilkko 2015). Liksom i föreliggande studie har man i tidigare forsk-ning funnit samband mellan social gemenskap och depressionssymptom.…”
Section: Diskussionunclassified
“…The (see Glass, 2012;Jolanki & Vilkko, 2015;Pedersen, 2015). Other examples of group living settings include assisted living facilities (see Jonsdottir, Jonsson, Sigurdard, & Ottir, 2015;Taylor & Neill, 2009), prisons (Wangmo et al, 2017), extended stay hotels (see Lewinson & Morgan, 2014), and…”
Section: Contiguous Settingmentioning
confidence: 99%
“…Research on conditions for older adults' well-being are not that common, but it has been suggested that older adults often estimate their health as relatively good, in spite of ill health. For example, Jolanki and Vilkko [23] believe this means that people over 90 change their health perspective. Health problems are perceived as normal, and medical problems are accepted and tolerated without complete loss of the sense of well-being.…”
Section: Introductionmentioning
confidence: 99%